Sacrifice in the Bronze Age Aegean and Near East: A Poststructuralist Approach - Recht, Laerke (Trinity College Dublin, 2007)
This project will provide a theoretical comparative analysis of the archaeological, iconographic and literary evidence concerning sacrifice in the civilisations of the Aegean and Near East in the Bronze Age. It will offer both an overview of the 'meaning' of sacrifice to the different civilisations in this period and a theoretical re-evaluation of the traditional archaelogical/anthropological approaches to Bronze Age sacrifice, in the light of poststructuralism and postmodernism.
Exhibited at the second Glucksman Memorial Symposium on June 13th 2007
Keywords: Bronze Age Aegean; Bronze Age Near East; Sacrifice